Assessment trial of the Polish countryside development five years after the accession to the European Union - Marciniuk-Kluska, Anna; Bombik, Antoni (Studia Ecologiae et Bioethicae, 2010)
The objective of this article is familiarisation with the issues relating to agricultural development in Poland and its perspectives for the future. A trial to assess the development of the Polish agricultural areas has been made five years after the accession to the European Union. The analysis has been performed on the basis of the data from Economical Accounts for Agriculture (EAA), the Central Statistical Office (GUS), and the Ministry of Agriculture and Rural Development (MRiRW). Chosen data on income and subsidies in the farm sector in Poland between 2003 and 2008 have been quoted. The analysis of the statistical data shows that farmers’ income after Poland’s accession to the EU has risen nearly twice but the financial situation of people living in the agricultural areas is still very diversified. Their income has increased thanks to the EU's direct subsidies. The integration between Poland and the European Union has created additional opportunities for growth in the food and agriculture sector. For five years of Polish membership in the EU the export of farm and food products has nearly tripled.